Angicos e a gnosiologia freireana no advento histórico e político da educação popular no Brasil - Silva, Silvânia Lúcia de Araújo (2015)
Between the late 1950s and early 1960s, Brazilian society was marked by the flourishing of social movements which sprung up all over the country. The mobilization of the Peasants Leagues (Ligas Camponesas) and rural workers in favour of the land reform, the strengthening of the trade unions, the creation of the Workers' General Command (Comando Geral dos Trabalhadores), the military associations and the effervescence of the student movement were typical of that time. Under the National-development approach, Brazil demanded changes in various fields; Paulo Freire considered it a favourable time for the necessary transformations in our country. Thus, by means of historical-documental evidence about the 40 Hours of Angicos, we pursued information and conjectural fragments about the heuristic process of what was the first experience in the construction of the Freirean gnosiology, like “hunters” (GINZBURG, 1989). As object of study, the event in Angicos allowed us to problematize, more concretely, knowledge that shaped the way people behaved and acted in the 1960s. By means of methodological effort, we approached the protagonists of this experience with two objectives. First, to position ourselves closer to the students, to their cultural and social locus; to listen to their discourse and memories; to learn the ways each one of them – in their “customs in common” (THOMPSON, 1998), – possibly already aimed to gain access to the world of written culture. Second, based on the Coordinators of Cultural Circle (Coordenadores de Círculo de Cultura), to reflect upon their social and political class position; to analyse their choices and the reach of the relational dimension in that experience (perhaps, somewhat unconsciously, as a cultural inheritance). In the intersection of this protagonism, we freely unveil the concept of Circle of Culture (Círculo de Cultura) through the idea of Circularity (BAKHTIN, 1970 apud GINZBURG, 2006), by analysing the praxis developed in the Angicos experience. This thesis defends the urgency of agreeing new orientations and experiences that reflect upon and design an updated concept of popular education, as a way to subsidize the education of young people and adults and its investigative and dialogical heritage. In this way, we argue that more than five decades after that ebullient moment in Brazilian education, part of those marks should be re-territorialized. After continuous reflection about what was generated there, perhaps greater richness could have been better explored in the popular education processes. As a result, we conclude that Angicos synthesizes educational inspirations that provide – politically and historically –, the systematization of ideas and the direction of what we know today as Popular Education, despite the contradictions involved in the fulfilment of its execution.